Oral health status and dental care for hospitalized patients with facial fractures (Research, Society and Development, 2021)
Objective: to analyze the oral health profile of inpatients victims of oral and maxillofacial trauma at the Institute Dr. José Frota Hospital, Ceará, Brazil. Methodology: a study carried out in 2020 started with an examination of the oral cavity at the bedside, application of the DMFT and The Bedside Oral Exam indexes, together with the survey of dental needs and application of the Oral Health Impact Profile Scale (OHIP-14), relating the findings, applying average, standard deviation and calculating Cronbach's alpha coefficient and Spearman's correlation for the OHIP-14 finding. Results: We evaluated 78 patients, mostly male (88%), with a mean age of 32.72 ± 11.63 years old, with hypertension being the most prevalent comorbidity. Besides, 60% of the sample had a fracture in the lower third of the face. The average number of decayed teeth per patient was 5.69. About 62.82% had poor oral health, seen from generalized biofilm and swollen gums. Low-Level Laser therapy was indicated for 94.8% of the sample, periodontal treatment in 58.9%, restorative therapy in 69.2%, and surgical in 42.3%. Regarding the OHIP-14 questionnaire, facial trauma negatively impacted the participants' quality of life, especially in dimensions related to pain. Conclusion: there was a significant prevalence of oral diseases, such as gingivitis and dental caries, which justifies the need for dental intervention before the maxillofacial surgical approach.